Spectrum of phenotype of ventricular noncompaction in adults. (September 2021) - Di Toro, Alessandro; Urtis, Mario; Giuliani, Lorenzo; Pizzoccheri, Roberto; Aliberti, Flaminia; Smirnova, Alexandra; Grasso, Maurizia; Disabella, Eliana; Arbustini, Eloisa
Abstract: Background: LVNC/LVHT is characterized by the presence of i) prominent left ventricular (LV) trabeculae; ii) a thin compacted layer; iii) deep inter-trabecular recesses. The in vivo diagnosis is exclusively based upon imaging (2D-TTE and CMR, CT when CMR is not feasible). Diagnostic criteria are based upon the non-compacted / compacted ratio in a variable number of cardiac segments. Prevalence varies from 1.28% with 2D-TTE to 14.89% with CMR in cohorts of cardiac diseases, controls, representative populations, athletes, non-cardiac diseases (renal, hematological, and neuromuscular diseases), and primigravida cohorts; the highest prevalence is in CMR non-cardiac cohorts (36.21%). Aim of review: To provide a summary of the now extensive literature giving key elements for the interpretation of LVNC/LVHT morphology in adults. Key scientific concepts of review: LVNC in adults may represent a dynamic and potentially reversible morphological trait. LVNC / LVHT remains a descriptive diagnosis that does not incorporate functional, dimensional, electrical, and biochemical diagnostic criteria. Isolated LVNC in hearts with normal LV function and dimensions does not fulfill the criteria to be defined cardiomyopathy. The terms "non-compacted cardiomyopathy" and "LVNC cardiomyopathy" should be discouraged based on the extensive evidence that the presence of hypertrabeculation does not necessarily imply mechanical/electrical dysfunction. Highlights: LVNC is described by a) prominent trabeculae; b) thin compacted layer; c) deep inter-trabecular recesses. In adults, LVNC can be acquired and reversible in pregnant women, athletes, renal, hematologic, muscle, and non-cardiac disorders. LVNC can associate with cardiomyopathies, all types, and CHD. Disease genes are those causing the underlying cardiac disease. In multiple and heterogeneous cohorts the prevalence varies from 1.28% with 2D-TTE to 14, 89% with CMR. The diagnosis is based upon the non-compacted/compacted ratio. There are no functional, electrical, or biochemical criteria.